Building Intelligent Transportation Cloud Data Center Based on SOA - Zhang, Wei; Qi, Qinming; Deng, Jing (International journal of ambient computing and intelligence, 2017)
This paper is targeted at issues including traditional stovepipe data center, low utilization of IT equipment and data resources as a result of rigid IT structure, high maintenance costs and high energy consumption in system operation. By taking Beijing Municipal Committee of Transport (BMCT)'s data center as an example, a way to establish distributed traffic cloud data center based on SOA (Service-Oriented Architecture) fused with cloud computing is introduced in this paper; in addition, network-aware energy conservation scheduling DENS (Data- center Energy-efficient Network-aware Scheduling) algorithm applied in cloud data center is put forward to realize the full utilization of all kinds of resources in the cloud data center. Experimental results also show the effectiveness of the proposed algorithm by comparing with traditional DENS algorithms.